Determinant of Antiretroviral Therapy Adherence Through the Health Belief Model Theory in People Living with HIV/AIDS: A Systematic Review - Supriyatni, Nani; Sumiati, Tati; Lestari, Tutik; Andiani, Andiani (Indonesian Journal of Global Health Research, 2024)
Human Immunodeficiency Virus (HIV) and Acquired immunodeficiency syndrome (AIDS) are still threats to public health. Indonesia ranks third highest in the number of people living with HIV/AIDS (PLWHA) and new infection cases in the Asia-Pacific region after India and China. One of the sustainable development targets to improve health and well-being is to end the AIDS epidemic by 2030 which refers to the global policy of "Getting to Zeros" using antiretroviral therapy (ARV). This study aims to analyze the determinants of HIV/AIDS treatment adherence through ARV therapy using the Health Belief Model (HBM) theory. Methods: This study used Preferred Reported Items for Systematic Reviews and Meta-Analyses (PRISMA) for systematic review through keyword searches on 10 relevant articles. Databases used include journals from ScienceDirect, Google Scholar, and PubMed. Article submission took place in May–June 2023. The article used is an article that contains research in the range of 2015–2023. Results and Discussions: The findings of the article are then screened, filtered, and critically appraised through several inclusion and exclusion criteria. The search results found as many as 10 suitable articles. The results showed a relationship between perceived barriers, perceived benefits, self-efficacy, and cues to action with adherence to ARV therapy in PLWHA. Non-adherence to ARV treatment has multidimensional consequences at both the individual, community, and policy levels. Individually, it can lead to an uncontrolled viral load, increasing the risk of resistance and other factors, including mortality. Conclusions: So it is necessary to increase awareness of the importance of ARV therapy for PLWHA through HBM theory. In addition, it is expected for the closest people to always provide positive support to PLWHA to be compliant in carrying out ARV therapy.